2017
DOI: 10.18632/oncotarget.21317
|View full text |Cite
|
Sign up to set email alerts
|

Juglanin inhibits lung cancer by regulation of apoptosis, ROS and autophagy induction

Abstract: Juglanin (Jug) is obtained from the crude extract of Polygonum aviculare, exerting suppressive activity against cancer cell progression in vitro and in vivo. Juglanin administration causes apoptosis and reactive oxygen species (ROS) in different types of cells through regulating various signaling pathways. In our study, the effects of juglanin on non-small cell lung cancer were investigated. A significant role of juglanin in suppressing lung cancer growth was observed. Juglanin promoted apoptosis in lung cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 82 publications
(104 reference statements)
0
28
0
1
Order By: Relevance
“…It has previously been demonstrated that PI3K/AKT signaling pathway can affect cell apoptosis through a variety of mechanisms, including promoting P53 nucleus translocation ( 28 , 31 ). In addition, PI3K/AKT can also modulate B cell lymphoma-2 associated agonist of cell death (Bad) activity, cause phosphorylation of caspase-9, block P53, and release apoptosis factors into the mitochondria ( 32 ). These mechanisms work together to block the process of programmed cell death, thus protecting the cells from apoptosis, promoting cell survival, and leading to the proliferation of tumor cells ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that PI3K/AKT signaling pathway can affect cell apoptosis through a variety of mechanisms, including promoting P53 nucleus translocation ( 28 , 31 ). In addition, PI3K/AKT can also modulate B cell lymphoma-2 associated agonist of cell death (Bad) activity, cause phosphorylation of caspase-9, block P53, and release apoptosis factors into the mitochondria ( 32 ). These mechanisms work together to block the process of programmed cell death, thus protecting the cells from apoptosis, promoting cell survival, and leading to the proliferation of tumor cells ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Juglanin demonstrated cytotoxicity on different models of breast (MCF-7, SKBR3, MDA-MB231 and BT474) [ 89 ], lung (A549, HCC827 and H1975) [ 90 ], and skin (UVB-stimulated B16F10) cancers. The fil rouge tracking juglanin’s antitumour potential is oxidative stress induction.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…The fil rouge tracking juglanin’s antitumour potential is oxidative stress induction. Indeed, the juglanin-mediated ROS (reactive oxygen species) accumulation drove apoptosis and autophagy in lung and breast cancer cells [ 89 , 90 ]. In both cancer types, juglanin triggered both the extrinsic and intrinsic pathway of apoptosis.…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Hücrelerin tepken hücre türlerinden temizlenmesi Atg7 hasarlı tümör hücrelerinde besin yetersizliğinde hayatta kalmayı sağlamaz. Böylece otofaji hücrenin sağkalımını sağlamada yetersiz kalırken sisteme substrat sağlayarak redoks dengesini korumada görev almaktadır 21,22 .…”
Section: Otofaji Aracılı Geri-dönüşümün Kanser Metabolizmasına Etkisiunclassified